Effects of irradiation source and dose level on quality characteristics of processed meat products. (January 2017) - Ham, Youn-Kyung; Kim, Hyun-Wook; Hwang, Ko-Eun; Song, Dong-Heon; Kim, Yong-Jae; Choi, Yun-Sang; Song, Beom-Seok; Park, Jong-Heum; Kim, Cheon-Jei
Abstract: The effect of irradiation source (gamma-ray, electron-beam, and X-ray) and dose levels on the physicochemical, organoleptic and microbial properties of cooked beef patties and pork sausages was studied, during 10 days of storage at 30±1 °C. The processed meat products were irradiated at 0, 2.5, 5, 7.5, and 10 kGy by three different irradiation sources. The pH of cooked beef patties and pork sausages was unaffected by irradiation sources or their doses. The redness of beef patties linearly decreased with increasing dose level ( P <0.05), obviously by e-beam irradiation compared to gamma-ray and X-ray ( P <0.05). The redness of pork sausages was increased by gamma-ray irradiation, whereas it decreased by e-beam irradiation depending on absorbed dose level. No significant changes in overall acceptability were observed for pork sausages regardless of irradiation source ( P >0.05), while gamma-ray irradiated beef patties showed significantly decreased overall acceptability in a dose-dependent manner ( P <0.05). Lipid oxidation of samples was accelerated by irradiation depending on irradiation sources and dose levels during storage at 30 °C. E-beam reduced total aerobic bacteria of beef patties more effectively, while gamma-ray considerably decreased microbes in pork sausages as irradiation dose increased. The results of this study indicate that quality attributes of meat products, in particular color, lipid oxidation, and microbial properties are significantly influenced by the irradiation sources. Highlights: The effect of three irradiation source and dose level on meat products was studied. The redness was significantly influenced by irradiation sources and dose levels. Lipid oxidation, and microbial properties also affected by irradiation sources.